2022
DOI: 10.24875/ric.22000072
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of uric acid/albumin ratio for the prediction of new-onset atrial fibrillation in patients with ST-Elevation myocardial infarction

Abstract: Background: There is a lack of studies supporting the association between the uric acid/albumin ratio (UAR) and the development of new-onset atrial fibrillation (NOAF) in ST-elevation myocardial infarction (STEMI) patients treated with primary percutaneous coronary intervention (pPCI). Objective: The objective of the study was to assess the efficacy of the UAR for predicting the occurrence of NOAF in STEMI patients undergoing pPCI. Methods: We recruited 1484 consecutive STEMI patients in this retrospective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…39 The UAR index was associated with the occurrence of atrial fibrillation and kidney injury. 40,41 Furthermore, Toprak et al 15 and Şaylık et al 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The UAR index was associated with the occurrence of atrial fibrillation and kidney injury. 40,41 Furthermore, Toprak et al 15 and Şaylık et al 16…”
Section: Discussionmentioning
confidence: 99%
“… 39 The UAR index was associated with the occurrence of atrial fibrillation and kidney injury. 40 , 41 Furthermore, Toprak et al 15 and Şaylık et al 16 have found that UAR was a superior marker in predicting poorly‐developed CCC in stable coronary heart disease. However, the relationship between the UAR and CCC development in NSTEMI patients remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, individuals with higher UAR values might exhibit increased susceptibility to inflammation, oxidative stress, and severe CAD compared with those with lower UAR values. Recent research has supported this idea and recognized UAR as a novel marker for inflammation and oxidative stress, which exhibits a robust correlation with cardiovascular disorders [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The uric acid-albumin ratio (UAR) – an innovative inflammatory and oxidative stress metric that combines UA and albumin measurements to reflect the body’s overall inflammatory and oxidative status – reportedly correlates with adverse cardiovascular prognostic events [ 11 13 ] and the severity of CAD [ 14 , 15 ]. However, no research has explored the association between UAR and the occurrence of ISR in individuals who undergo DES placement.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a retrospective analysis of 402 STEMI individuals treated with PCI had demonstrated that SII can independently predict NOAF [ 31 ]. A retrospective and cross-sectional investigation of 1484 STEMI individuals following PCI conducted by Selçuk et al had displayed that the value of uric acid/albumin can independently predict the development of NOAF [ 32 ]. Another recent investigation concluded that SII is an independent predictor of postoperative AF after analyzing 391 consecutive cases treated with isolated coronary artery bypass grafting and also demonstrated that the predictive role of SII is superior to that of NLR or platelet to lymphocyte ratio[ 33 ].…”
Section: Discussionmentioning
confidence: 99%